Foot Orthoses for People With Rheumatoid Arthritis: a Survey of Prescription Habits Among Podiatrists - Chapman, L; Redmond, AC; Landorf, K; Rome, K; Keenan, AM; Waxman, R; Alcacer-Pitarch, B; Siddle, H; Backhouse, M (BioMed Central, 2019)
Background Guidelines recommend foot orthoses for people with both early (< 2 years) and established rheumatoid arthritis (RA). While prefabricated foot orthoses are cheaper and can exhibit comparable effects to customised devices, the available evidence for their effectiveness is inconsistent. Little is known about what types of foot orthoses clinicians prescribe. This study describes the foot orthoses prescription habits of podiatrists for people with rheumatoid arthritis. Methods One hundred and eighty-three podiatrists from the United Kingdom (UK) (n = 88), Australia (n = 68) and New Zealand (n = 27) completed a self-administered, online survey regarding the types of foot orthoses prescribed in clinical practice for people with RA. This study forms part of a wider international survey exploring foot orthosis prescription habits. Results UK respondents were more likely to prescribe prefabricated orthoses for early RA (n = 47, 53%) and customised orthoses for established RA (n = 47, 53%). Respondents in Australia were more likely to prescribe customised orthoses for both early (n = 32, 47%) and established (n = 46, 68%) RA, whilst respondents in New Zealand were more likely to prescribe prefabricated orthoses for both early (n = 16, 59%) and established (n = 10, 37%) disease. Irrespective of disease stage, the use of foam impression boxes was more prevalent in the UK and New Zealand when capturing a model of the feet prior to manufacturing customised orthoses. In contrast, electronic scanning and plaster of Paris were more common in Australia. Computer aided manufacture was utilised more frequently among respondents in Australia than in the UK and New Zealand. Respondents in all three countries specified more flexible shell materials for established RA, compared to early disease. Cushioning top covers (e.g. PORON® or polyurethane) were most frequently specified in all countries for both disease stages. Conclusions Considerable variation was seen in the self-reported foot orthoses prescription habits of respondents for people with RA. Variation between countries and disease stage was seen in type of orthoses, specific brands, manufacturing methods, and materials prescribed. The results allow podiatrists and broader health service providers to compare their practice against reported national and international patterns.
Keywords: Foot; Orthotic devices; Orthoses; Rheumatoid arthritis; Podiatry